Bleeding and clotting in hereditary hemorrhagic telangiectasia - Dittus, Christopher (World J Clin Cases, 2015)
Hereditary hemorrhagic telangiectasia (HHT) is a relatively common inherited vascular disorder that was first described in 1864, and is notable for epistaxis, telangiectasia, and arterial venous malformations. While genetic tests are available, the diagnosis remains clinical, and is based on the Curacao criteria. Patients with HHT are at increased risk for both bleeding and clotting events. Because of these competing complications, hematologists are often faced with difficult clinical decisions. While the majority of management decisions revolve around bleeding complications, it is not infrequent for these patients to require anticoagulation for thrombosis. Any anticoagulation recommendations must take into account the bleeding risks associated with HHT. Recent reviews have found that HHT patients can be safely anticoagulated, with the most frequent complication being worsened epistaxis. Large clinical trials have shown that factor IIa and Xa inhibitors have less intracranial bleeding than warfarin, and basic coagulation research has provided a possible mechanism. This article describes the anticoagulation dilemma posed when a 62-year-old female patient with a history of bleeding events associated with HHT was diagnosed with a pulmonary embolism. The subsequent discussion focuses on the approach to anticoagulation in the HHT patient, and addresses the role of the new oral anticoagulants.